Analysis Of The Impact Of Zero Waste Fashion On The Environment And Business Development In The Home Industry Of Yasmin Wiwid Eco-Print Sustainable Fashion, Pesawaten District Perspective Of Islamic Business Ethics - Dimas Kurniawan; Budimansyah Budimansyah; Muhammad Iqbal Fasa; Is Susanto (LPPM Universitas Multi Data Palembang, 2023)
Textile and industry fashion is one of the largest economic sectors in Indonesia, supported by increasingpublic interest in fashion products at home and abroad and the circulation of trends that are increasingly dynamicevery year. The increasingly diverse segmentation of textile and fashion products also supports the acceleration of theeconomy and creative industries in Indonesia. With the development of the textile and fashion industries, the presenceof waste in the manufacturing process is unavoidable. Therefore, the objectives of this research can be formulated,namely to find out the analysis of the effect of Zero Waste Fashion on the environment and business development,whether it is able to fix all existing problems, especially to minimize waste on the environment and also assist in thebusiness development process. This research is a type of qualitative descriptive research. This research was conducted at Yasmin Wiwid’s home industryEcoprint Sustainable FashionPesawaran Regency, by collecting and studying data obtained from observations and interviews with data triangulation so as to obtain a research objective to beachieved. Based on the analysis of existing facts and data, the authors conclude that the implementation of Zero WasteFashion is capable of having a positive impact on the environment and a positive effect on the business developmentprocess as seen from various assessment parameters and success indicators used and in accordance with the principles existing in Islamic business ethics and also some existing theoretical assumptions such as Theory of PlannedBehavior, Environmental Awareness Purchase Intention Model and Biocentric Theory.